Evaluating the Role of Green Financing, International Trade and Alternative Energies on Environmental Performance in Case of Chinese Provinces: Application of Quantile Regression Approach - Hoang, Dinh Cong; Tuan, Dinh Cong (International Journal of Energy Economics and Policy, 2023)
Despite increasing recognition of the urgent need to address the impacts of climate change, the global response has been inadequate, and greenhouse gas emissions continue to rise. The role of green financing in addressing this problem is uncertain, as it remains in its early stages of development and implementation. Furthermore, the relationship between green financing, alternative energies, and environmental performance is complex and not well understood. This study examines the potential of green financing as a tool for mitigating the effects of climate change and promoting sustainable development. Assessing the effectiveness of green financing as a means of improving environmental performance, and the role of alternative energies in this relationship. This study aims to provide recommendations for policymakers, businesses, and other stakeholders on how to effectively leverage green financing to promote sustainable development and address the impacts of climate change. Using Quantile regression approach, this study finds that green finance, international trade, GDP and alternative energies are important determinants of CO2 emissions of China. We find that green finance, and alternative energies have negative location coefficients, which imply that these factors abate CO2 emissions. On the contrary, the location coefficient of international trade and GDP are positive, which suggest that these factors increase CO2 emissions of China. The negative coefficient of green finance for all quantiles implies that green finance is beneficial for environmental performance of China.